The clinical features of COVID - 19 in a group of Iraqi patients: A record review - Dawood, Haider; Hwayyiz, Ayad; Ibrahim, Ibrahim; Abdul Rahman, Imad (Journal of the Faculty of Medicine Baghdad, 2021)
Background: The number of coronavirus infection cases has increased rapidly since early reports in the December 2019 in China. But data on the clinical features of infected peoples is variable from one country to the other.Objective: Studying clinical features of patients with a positive RT PCR COVID – 19, in a group of Iraqi patients.Results: The study included 200 patients with 133 (66.5%) males and 67 (33.5%) females, and age range of 14- 89 years, with mean age 46.4 years. A history of contact with a COVID -19 positive case was found in 80 patients (40%), Ischemic Heart Disease in 11 patients (5.5%), hypertension 34 (17%), diabetes mellitus 36 patients (18%). The most frequently seen age group was between 21-39 years (76 patients - 38%). The most frequently seen symptoms were fever 76.5% and generalized weakness 73%. A statistically significant association was found between age and dyspnea (p = 0.014) and also diarrhea (p = 0.035), as well as between gender and rhinorrhea (p = 0.08) and nausea and/ or vomiting (p = 0.005).Patients and Methods: This is a record review study of 200 patients with a confirmed COVID - 19, conducted in Al Imamain Al Kadhimain Medical City from 1 May to 30 August 2020, the diagnosis of patients during this period. Data about demographic and the clinical characteristics have been recorded.